Lubrication Performances of Carbon-Doped MoSe2 Nanoparticles and Their Biocompatibility Characterization In Vitro - Wang, Lisha; Hou, Tao; Li, Yihong; Lu, Hailin; Gao, Li (Frontiers in Chemistry, 2021)
Currently, health and environmental protection issues have become a major focus area in many research and development projects. In this context, the recent MTT cytotoxicity assessment indicating that carbon-doped MoSe2 nanoparticles exhibit good biocompatibility has attracted considerable interest from researchers around the world. In this study, we report the successful synthesis of carbon-doped MoSe2 nanoparticles via the ultrasonic method, enhanced lubrication effect as oil additives. The tribology results confirmed that carbon-doped MoSe2 nanoparticles reduce the friction coefficient as well as adverse wear conditions. It was found that carbon-doped MoSe2 nanoparticles are smaller than untreated MoSe2 nanoparticles and can easily access the contact area and form a tribo-film to reduce friction and wear. Moreover, carbon-doped MoSe2 nanoparticles and their waste water have good biocompatibility. Hence, they could find practical application as oil additives.